Bumps and detours of the domestic pathway of money laundering legislation (Academic Journal of Internal Affairs, 2024)
Aim: The aim of the paper is a brief review of the past 30 years of domestic legislation concerning the criminal act of money laundering, also to summarise the lessons learned from the modifications and to outline some aspects of legal-interpretation.Methodology: The paper analyses the periodical changes of the phrasing of the act and the legal policy intentions in connection with these changes. It takes a position on the academic debates concerning the application of the offence and critically assesses legal practice.Findings: The current legislation and practice of money laundering is still not without inconsistencies. Qualification of specific acts as money laundering could often contradict fundamental legal principles, the proper interpretation of actual or pseudo multiple-offence theory, the concurring aspects of aiding and abetting versus subsidiary or collateral offences, and the necessity to justify culpability or mens rea. While not disputing the legitimate purpose of the offence, nevertheless with an expectation of a more critical attitude regarding its application, effective investigation of the preliminary offences shall not be de-emphasised, as its effectiveness is still the most effective way to the prevention of money laundering.Value: The conclusions may contribute to a better founded jurisprudence concerning money laundering, as well as it may provide guidance for future codification considerations.
Keywords: money laundering; unpunished subsequent offence; covert offending; intent